Potential impacts for monitoring sustainability: case study of hollow fiber membrane - Mahmood, Salwa; Mat Saman, Muhamad Zameri; Hemdi, Abdul Rahman; Zakuan, Norhayati (Medwell Publications, 2017)
Sustainability level is a new indicator of quality and efficiency for product life cycle. Sustainability should be balanced among Triple Bottom Line (TBL) aspects namely environmental, economic and social elements. For monitoring the sustainability of product, a comprehensive framework considering potential impacts for sustainability assessment should be developed. Previously, several studies presented frameworks to assess the sustainability level. However, few studies relate their frameworks with the potential impact of all TBL. Determination of potential impacts with its parameter is important during framework development. Potential impacts for environmental such global warming, acidification and eutrophication should be taken seriously. In this study, potential impacts for each sustainability aspects are shown. For the case study of hollow fiber membrane the potential impacts were obtained from primary and secondary data such product specification, bill of materials, literature reviews and help of GaBi Software.